Insight the influence of the catalyst basicity on glycolysis behavior of Polyethylene terephthalate (PET) - Pham, Duong Dinh; Cao, Anh Ngoc T.; Senthil Kumar, Ponnusamy; Nguyen, Tram B.; Nguyen, Ha Tran T.; Pham, Thuy Phuong Thi; Nguyen, Dang Le Tri; Nabgan, Walid; Trinh, Thanh H.; Vo, Dai Viet N.; Nguyen, Tung Manh (Elsevier Ltd, 2023)
Although polyethylene terephthalate (PET) is one of the most prevalent plastics, a cumulative disposal of PET waste has caused adverse effects on both economy and environment. Catalytic glycolysis of PET waste has emerged as a prevalent and sustainable pathway to address this problem. Due to the limitations of recovery and recycling, the catalytic development trend for PET glycolysis has recently changed from homogenous to heterogeneous designs. Herein, metal oxides with different basicity, including calcium, cerium, and cobalt, were supported on alumina and first employed in the glycolysis process of waste PET plastic. A plausible mechanism is proposed and reveals the correlation between the basicity of as-prepared catalyst and glycolysis performances. Among these catalysts, 10%Ce/Al2O3 exhibited a complete conversion of waste PET with the highest selectivity to the main product BHET. There is no significant drop in catalytic activity after five consecutive runs. Furthermore, the excellent quality of the monomer product BHET was confirmed via different analysis techniques. This work has contributed to a promising notion for engineering efficient heterogeneous catalysts of PET recycling technology.